2016
DOI: 10.1155/2016/6797851
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Vanadium Pentoxide and Antioxidants (Ascorbic Acid and Alpha‐Tocopherol) on Apoptotic, Cytotoxic, and Genotoxic Damage in Peripheral Blood of Mice

Abstract: This study was conducted to investigate the effects of vanadium pentoxide (V2O5), ascorbic acid (AA), and alpha-tocopherol (α-TOH) on apoptotic, cytotoxic, and genotoxic activity. Groups of five Hsd:ICR mice were treated with the following: (a) vehicle, distilled water; (b) vehicle, corn oil; (c) AA, 100 mg/kg intraperitoneally (ip); (d) α-TOH, 20 mg/kg by gavage; (e) V2O5, 40 mg/kg by ip injection; (f) AA + V2O5; and (g) α-TOH + V2O5. Genotoxic damage was evaluated by examining micronucleated polychromatic er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Our data also revealed that ascorbic acid was able to reduce meglumine antimoniate-induced genomic damage, corroborating previous studies that observed a protective effect of ascorbic acid against mutagenic damage induced by other stressors such as cyclophosphamide (44), arsenic trioxide (45), 3,5-dimethylaminophenol (46), and vanadium pentoxide (47). Ascorbic acid is a nonenzymatic antioxidant obtained from the diet and is essential to humans due to its participation in several physiological activities (48).…”
Section: Discussionsupporting
confidence: 91%
“…Our data also revealed that ascorbic acid was able to reduce meglumine antimoniate-induced genomic damage, corroborating previous studies that observed a protective effect of ascorbic acid against mutagenic damage induced by other stressors such as cyclophosphamide (44), arsenic trioxide (45), 3,5-dimethylaminophenol (46), and vanadium pentoxide (47). Ascorbic acid is a nonenzymatic antioxidant obtained from the diet and is essential to humans due to its participation in several physiological activities (48).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it has been proposed that the chemopreventive properties of antioxidants are related to their ability to target speciic cellular signaling pathways that regulate cellular proliferation and apoptosis [43]. This proposal is consistent with our results since the frequencies of apoptotic cells (particularly, late apoptotic cells) indeed increased signiicantly with the administration of vitamin C, and their administration prior to treatment of V 2 O 5 increased them even further [8]. Additionally, other studies have reported that the apoptosis-inducing activity of antioxidants might be synergistically enhanced by a combined treatment with chemopreventive [44] or genotoxic agents [40].…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Fromsupporting
confidence: 91%
“…Additionally, the promising low costs of vanadium-based drugs make it particularly atractive, and the ability to overcome the adverse efects of vanadium compounds during therapeutic action is an urgent and crucial issue for its future use in medicine [49]. Our indings strongly suggest that vitamin C can be used efectively in therapy either alone (antioxidant) or in combination with other agents such as V 2 O 5 to reduce their genotoxicity [8].…”
Section: Protective Efects Of Vitamin C Against Genotoxic Damage Frommentioning
confidence: 90%
See 2 more Smart Citations